اتجاهات اساتذة التعليم الابتدائي نحو استراتيجية التعلم التعاوني دراسة ميدانية بمجموعة من مدارس ابتدائية مدينة الأغواط - زهراء دمانة; خلود بن فرحات; محمد الصافي (My University, 2022)
The aim of this study is to identify the attitudes of teachers toward cooperative learning and to know the role of variables (gender, experience, profession). In this study, we relied on the descriptive approach that this approach describes the phenomenon in its present state and analysis The example size of the study was 41 persons distributed among primary school teachers femals and mals. In this study, we used the Lina Ali Scale .from the University of Damascus Journal - Volume 27 - Supplement - 2011 The study found the following results The results showed that the attitudes of the example towards cooperative learning are generally negative. There were no statistically significant differences in gender / seniority* key words : - directions - Cooperative learning